Assessing the Impact of Vaccination on Controlling the Spread of Human Scabies. (28th March 2013) - Bhunu, C. P.; Mushayabasa, S.; Monera, T. G.
Abstract : Scabies is among the infestations almost forgotten due to its association with poor communities. We formulate a deterministic model to assess the possible impact vaccination will have on scabies control. The Descartes's rule of signs is used to show the nature of the endemic equilibria. Analysis of the reproduction number and numerical simulations suggest that vaccination in addition to treatment will help greatly in reducing the spread of scabies infestation. This suggests there is a strong need for researchers to come up with a possible vaccine in that order to effectively control scabies especially among the disadvantaged communities.